Kajian Literatur : Penerapan Internet of Things (IoT) untuk Optimasi Manajemen Kesehatan Tanah - Albert Donatus Simamarta; Vasthi Khoirun Nisa; Rafly Maulana; Najwa Parawansa; Imelda Khairunnisa; Yeni Budiawati (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
This study aims to describe the application of Internet of Things (IoT) technology in optimizing soil health management through a systematic literature review. This research compares various IoT implementations for monitoring soil moisture, pH, and nutrients based on previous studies, and identifies differences in technological approaches, sensors used, and automation levels. The review results indicate that although IoT technology is proven effective for real-time soil condition monitoring and supporting precision agriculture, its implementation varies significantly between advanced systems with full automation developed internationally and simpler, local monitoring systems in Indonesia. The comparison shows that wireless inductive moisture sensors are superior in accuracy and corrosion resistance compared to conductive sensors. A TDS sensor-based hydroponic nutrient monitoring system demonstrated high accuracy with an average error of 4.7468% , while soil pH monitoring achieved an accuracy with a Mean Absolute Error (MAE) of 0.14. Furthermore, automated watering systems proved to reach a success rate of up to 93.75%. This review concludes that adapting low-cost wireless sensor system models has great potential for improving the efficiency of soil management in Indonesia, despite facing challenges in infrastructure and digital literacy.